Egg Components in Balut Produced from Three Itik-Pinas (IP) Mallard Breeds in the Philippines - Bondoc , O.L.; Ebron, A.O.; Ramos, A.R.; Santiago, R.C. (International Journal of Poultry Science, 2022)
Background and Objective: Balut is a popular Filipino food made from boiled mallard egg containing a developing embryo. The technical characteristics of balut are not well known and understood. This study aimed to compare the egg composition, shell thickness and egg shape dimensions of two types of balut- at 15 days of incubation (B15d) and 18 days of incubation (B18 d), produced by Itik-Pinas (IP) duck breeds (IP-Itim, IP-Khaki and Kayumanggi-IP). Materials and Methods: A total of 434 balut out of 524 randomly collected eggs from three IP breeds were produced using an artificial incubator. Balut characteristics were analyzed by least square procedures for unbalanced data to account for the effects of breed, balut type, “breed×balut type” interaction and duck hen’s age on the composition, shell thickness and egg shape dimensions of balut. Results: Balut is comprised of the developing embryo (23.70%), yolk (32.54%), albumen (16.24%), fluid portion (9.87%) and shell (17.73%). B15d balut had significantly (p<0.01) lower embryo weight and higher weight of yolk, albumen, fluid and shell than B18d balut. Shell thickness, short and long circumference and long-short circumference ratio was not different between B15d and B18d balut. IP-Itim had the lowest embryo weight (6.6 g) and highest yolk weight (22.3 g) in B15d balut. Kayumanggi-IP had the lowest albumen weight (13.7 g) in B15d balut and lowest embryo weight (20.3 g) in B18d balut. Albumen weight and yolk weight in B18 balut were not significantly different among the IP duck breeds (p>0.05). Conclusion: The technical characteristics of B15d and B18d balut may be considered in the choice of breed to be used in balut production according to consumer preferences.